Preservice teachers’ identity construction: emergence of expected and feared teacher-selves - Sallı, Ayşegül; Vanci Osam, Ulker (Springer Netherlands rbk@louisiana.edu, 2018)
Very little research has focused on the development of preservice teachers’ professional identity formation in a blog environment. Informed by possible-selves theory, this study focuses on how 15 preservice English language teachers’ blogging engagements influenced their expected and feared teacher-selves. Data was comprised of the participants’ reflective blog postings on their and their peers’ videorecorded teaching practice experiences, their blog interactions, and semi-structured interviews. Results of the qualitative data analysis illustrate how preservice English language teachers are inspired by both examples of ‘good’ teaching as well as by examples of how other teachers manage similar challenges. Participants articulated a greater scope of expected teacher-selves relevant to interpersonal relationships, instructional strategies, and professional qualities based on examples of ‘good’ teaching. Observation of peers who encountered similar obstacles during teaching practice lessons, however, led participants to generate feared teacher-selves focused mainly on classroom management and instructional strategies. These feared teacher selves were more limited in scope, however, vis-à-vis the expected teacher selves generated based on “good” teaching examples. © 2017, Springer Science+Business Media B.V.
Keywords: Blogging; Identity construction; Possible-selves theory; Preservice teacher education